EFECTO DE LA APLICACION DE DIFERENTES ABONOS ORGANICOS Y FERTILIZANTES QUIMICOS EN LA PRODUCCION DE TOMA¬TE (Lycopersicum sculentum Mill) EN UNA ZONA DEL DEPARTAMENTO DE NARIÑO - Córdoba U., Alvaro Javier; Chaves J., Germán Ernesto; Montenegro Galvez, Victor (Revista de Ciencias Agrícolas, 1987)
En una zona del clima medio del Departamento de Nariño se realizó un trabajo con el fin de determinar la respuesta del tomate a la fertilización edáfica con diferentes abonos de origen vegetal y animal y fertilizante químico 10 30-10. Los tratamientos fueron: A. Químico: 1050 k/ha de 10-30-10 a la semana del trasplante +150 kg de úrea, 2 semanas antes de la floración.B. Gallinaza + N-P-K toda la dosis antes del trasplante; C. Gallinaza + N-P-K, 50% de la dosis 30 días antes del trasplante y la otra mitad 50 días después. D. Residuos de fique + N-P-K, toda la dosis 30 días antes del trasplante. Residuos de fique + N-P-K 50% de la dosis 30 días antes del trasplante y la otra mitad 50 días después. F. Estiércol + N-P-K, toda la dosis 30 días antes del trasplante. G. Estiércol + N-P-K 50% de la dosis 30 días antes del trasplante y el resto 50 días después. H. Testigo, sin fertilizante. Las dosis correspondieron a 8 t/ha de cada abono orgánico + 400 kg 15-15-15. Se encontró que los tratamientos en base a abonos orgánicos y químicos produjeron incrementos estadísticamente significativos en diámetro de frutos y producción de tomate. El mayor diámetro promedio de frutos (7,16 cm) y la mayor producción (22,38 t/ha) se consiguió en el tratamiento en base a gallinaza + n-p-k, toda la dosis 30 días antes del trasplante. La menor producción y el menor promedio de diámetro de frutos correspondió al tratamiento testigo. ABSTRACT This work was carried out to determine the tomato response to edaphic fertilization, using organic fertilizers (animal and plant) and 10-30-10 fertilizer, in a zone of the temperate climate. The treatments applied were: A. 1050 kg of 10-30-10 fertilizer per hectares, applied one week after the trans plantation, plus 150 kg of urea, applied 2 week before flowering. Heng during plus n-p-k, applied 30 days before the transplantation. C. Heng during plus n-p-k, applied 50%, 30 days before the transplantation and 50%, 20 days after the transplantation. D. Common American agave residues plus n-p-k applied 30 days before the transplantation. e. Common American agave residues plus n-p-k applied 50%, 30 days before the transplantation and 50%, 20 days after the transplantation. F. Manure plus n-p-k applied 30 days before the transplantation. G. Manure plus n-p-k applied 50%, 30 days before the transplantations and 50%, 20 days after the transplantation. H. Control, without fertilization. The organic fertilizers were applied at a rate of 8 t/ha, and the n-p-k at a rate of 400 kg of 15-15-15 fertilizer/ha. Signification differences in fruit diameter and fruit production were found for all the treatments with organic and chemical fertilizer. The higher average in diameter of fruits (7,16 cm) arid the higher production of tomate fruits (22,38 t/ha) was jound in the treatment with heng during plus n-p-k applied 30 days before the transplantation the lower production corresponded to the control.